Pelaksanaan Kunjungan Rumah Dalam Mengatasi Masalah Keterlambatan Siswa di Sekolah SMA YP Utama Medan - Ade Chita Putri Harahap; Rizki Rahmayani Ritonga; Suvika Syahputri; Apriana Dewi; Indri Kurnia Dewi; M. Ali Batubara (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Home visits are very important if students' problems cannot be handled by the school. So this will make the counseling teacher to make home visits to students who do not obey or even carry out the warnings given by the guidance counselor and other teachers. This home visit was carried out to find out the causes of what happened so that students were late to come to school and also to find out the source of data from parents of students who had problems. In carrying out research in the Field Experience Practice (PPL-1) we used observation and interview methods as instrumental tools. During this research we found several cases that occurred at SMA YP UTAMA MEDAN. One of them is the delay of students to school. We also saw how the teacher's lack of attention to students at the school resulted in a lack of discipline in the time of the students. The teacher at SMA YP UTAMA MEDAN was also less assertive in reprimanding students who made trouble at school. As we know the attention of teachers in schools to students is needed. Because with the teacher's attention to students, students will feel comfortable and will be more obedient to the warnings given by these students. Keywords: Students, home visits, tardiness, counseling teachers, schools